Analysis of Operative Morbidity in a Single Center Initial Experience with Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy. Issue 1 (January 2014) - Graziosi, Luigina; Mingrone, Elvira; Marino, Elisabetta; Cavazzoni, Emanuel; Donini, Annibale
Background: Peritoneal carcinomatosis has been traditionally considered a rapidly lethal disease and consequently managed by merely palliative options. In the last decade, the clinical interest in the condition has increased because encouraging results have been reported in association with a new treatment strategy that combines cytoreductive surgery and hyperthermic intraperitoneal chemotherapy. Relatively high rates of severe complications are generally associated to this complex procedure. Our aim was to analyze treatment-related morbidity in our institutional initial experience. Materials and Methods: Since October 2006, 36 hyperthermic intraperitoneal chemotherapy plus cytoreductive surgery procedures have been carried out in our Department. Patients treated showed abdominal malignancies and ovarian cancer with peritoneal carcinomatosis. Only 9 patients were treated with prophylactic treatment for gastric cancer at high risk to develop peritoneal carcinomatosis. Results: In 27 patients, a macroscopically complete cytoreduction was done. The overall morbidity was 75%. Grades IV and V represented only 11.1%. Conclusions: Rigorous preoperative workup and strict selection criteria allowed a successful safe start of a new program of cytoreductive surgery and hyperthermic intraperitoneal chemotherapy in a general surgery unit.